Pendekatan Kontekstual dalam Pembelajaran Konsep Keliling Lingkaran di Sekolah Dasar - Meika Adila; Nur Jia Azizah; Neza Agusdianita (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to describe the teaching strategies used by teachers in introducing the concept of a circle’s circumference in elementary school. The research employed a descriptive qualitative approach using observation and interviews with a sixth-grade teacher at SDN 85 Bengkulu City. Data were collected through classroom observations and interviews, then analyzed descriptively. The findings show that the teacher implemented experiential learning by engaging students in observing and measuring circular objects around them. This strategy helped students understand the relationship between circumference and diameter without merely memorizing formulas. The teacher also made use of concrete teaching aids, interactive images, animated videos, and GeoGebra applications to strengthen conceptual understanding. Challenges encountered included students’ difficulty in distinguishing radius and diameter as well as understanding the symbol π (pi). The study concludes that the teacher applied contextual learning strategies supported by various media and learning resources.